Requirements for implementing cloud computing in accounting education in Libya: a study on faculty members in the accounting department at the universities of Sabratha and Zawiya (Al-Farooq Journal of Sciences, 2026)
The primary objective of this study was to identify the requirements for implementing cloud computing in accounting education programs within the Accounting Departments of the Faculties of Economics at the universities of Sabratha and Zawiya. To achieve this objective, the researcher adopted the descriptive research approach and utilized statistical analysis through the (SPSS) Statistics program. The study reached several key findings, the most significant of which indicated—based on the responses obtained from the research participants—that there are a number of essential requirements that must be available for the implementation of cloud computing in accounting education. These requirements include: infrastructure requirements, human requirements, administrative and organizational requirements, and legislative and legal requirements. The researcher also recommended the necessity of striving to implement such technologies in higher education institutions in general by providing an appropriate environment for their application. Furthermore, the study emphasized the importance of government support for the development of higher accounting education through evaluating the current situation, addressing existing shortcomings, and introducing modern improvements that align with both local and international labor market requirements.
Keywords: cloud computing - accounting education – Ai - E-accounting education